Integrated G Proteins Signaling in Plants - Yalovsky, Shaul; Baluška, František; Jones, Alan (Signaling and Communication in Plants,, 2010)
This volume focuses on structure, function and regulation of plant signaling G proteins and their function in hormonal pathways, polarity, differentiation, morphogenesis and responses to biotic and abiotic stresses. Plants are sessile organisms that need to continuously coordinate between external and internal cues. This coordination requires the existence of hubs to allow cross-talk between different signaling pathways. A single family of Rho GTPases termed either ROPS or RACs and heterotrimeric G proteins have emerged as the major molecular switches in multitude of signal transduction pathway in plants.